Antioxidant, anti-obesity, and lipid-lowering properties of Philippine "duhat" (Syzgium cumini L. skeel) freeze-dried fruit flesh - Mercado, Carmela Jhoy G.; Atienza, Liezl M.; Sunico, Dianne Jane A.; Maniwang, Jonna Rose C.; Gapasin, Roxanne P.; Gaban, Prince Joseph V.; Castillo-Israel, Katherine Ann T.; Cena-Navarro, Rohani; Estacio, Maria Amelita C. (Vol. 150, No. 4 (August 2021) pages 793-808.)
"Philippine indigenous berries are known as rich sources of antioxidants that may promote health and prevent the occurrence of diseases. Thus, the study investigated the nutritional, antioxidants, anti-obesity, and lipid-lowering properties of freeze-dried "duhat" (FDD) (Syzgium cumini L. Skeel) fruit using proximate analysis, in vitro antioxidant assays, and in vivo efficacy using obese diet-induced ICR mice, respectively"-Title page.